2010
DOI: 10.1007/s10008-010-1233-3
|View full text |Cite
|
Sign up to set email alerts
|

Simulation of a mixed-conducting membrane-based gas turbine power plant for CO2 capture: system level analysis of operation stability and individual process unit degradation

Abstract: A gas turbine power plant for CO 2 capture, based on oxygen-permeable membranes with mixed ionicelectronic conductivity, was analysed with respect to longterm stability by means of numerical simulation. Due to the attractive transport and physicochemical properties of mixed-conducting La 2 NiO 4+δ , this nickelate was selected as a prototype membrane material for this application. Experiments showed very slow degradation of La 2 NiO 4+δ membranes at oxygen chemical potentials close to atmospheric conditions, w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 47 publications
0
3
0
Order By: Relevance
“…In reality, measured variables may vary due to measurement errors. Furthermore, the turbomachinery and the membrane reactor components are exposed to degradation, and changes in ambient conditions also have a strong effect on the power plant performance …”
Section: Load-control Strategiesmentioning
confidence: 99%
“…In reality, measured variables may vary due to measurement errors. Furthermore, the turbomachinery and the membrane reactor components are exposed to degradation, and changes in ambient conditions also have a strong effect on the power plant performance …”
Section: Load-control Strategiesmentioning
confidence: 99%
“…71,72 After the chemical failure of membranes ( e.g. , formation of carbonates or binary phases), 73–76 closed-loop chemical recycling appears favourable to fulfil the high quality and security standards. 77–79…”
Section: Introductionmentioning
confidence: 99%
“…3 End-of-life membranes would be an easily recoverable, high-quality waste with well-defined composition and valuable components. 71,72 After the chemical failure of membranes (e.g., formation of carbonates or binary phases), [73][74][75][76] closed-loop chemical recycling appears favourable to fulfil the high quality and security standards. [77][78][79] A promising Ruddlesden-Popper (RP) phase membrane material (La 0.9 Ca 0.1 ) 2 Ni 0.75 Cu 0.25 O 4±δ (LCNC) was recently developed by Chen et al 80 LCNC showed a sufficient oxygen permeation flux of 0.63 mL min −1 cm −2 at 900 °C for a 0.65 mm thick membrane under both, air/helium and air/CO 2 gradient.…”
Section: Introductionmentioning
confidence: 99%